2013
DOI: 10.1016/j.triboint.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Microtexture based analysis of surface asperity flattening behavior of annealed aluminum alloy in uniaxial planar compression

Abstract: X. (2013). Microtexture based analysis of surface asperity flattening behavior of annealed aluminum alloy in uniaxial planar compression. Tribology International, Microtexture based analysis of surface asperity flattening behavior of annealed aluminum alloy in uniaxial planar compression AbstractDuring the uniaxial planar compression of annealed aluminum alloy, a novel approach to determine surface asperity flattening (roughness Ra) is employed by analyzing the evolution of surface microtexture. With an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…1), aluminum alloy 6061 samples were compressed on a channel die [19,21], while samples were constrained in the transverse direction. In order to reduce the influence of tool, the compressing tool is polished smoothly (roughness is about 10 nm) and flat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), aluminum alloy 6061 samples were compressed on a channel die [19,21], while samples were constrained in the transverse direction. In order to reduce the influence of tool, the compressing tool is polished smoothly (roughness is about 10 nm) and flat.…”
Section: Methodsmentioning
confidence: 99%
“…So the surface roughness evolution in most constrained deformation is really a surface asperity flattening process [17]. In recent years, Li et al [18][19][20][21][22][23] employed crystal plasticity theory to develop a 3D surface asperity flattening model to simulate the practical constrained deformation process, analyzed the relationship between the surface asperity and reduction, friction and texture. It was found that during the normal CUPC process surface roughness evolution of workpiece is proportional to gauged reduction, friction plays an important role in surface asperity flattening by decreasing the surface roughness and increasing micro hardness and flow stress.…”
Section: Introductionmentioning
confidence: 99%
“…There are different stages in the evolution of hardness because when the reduction is lower (less than 60%), increasing the strain rate generally increases the hardness. At a larger reduction, increasing the strain rate will decrease the hardness under the same reduction [23]. When the reduction is lower, increasing the strain rate can increase the shearing rate of slip systems and also increase the density of dislocation.…”
Section: Three-dimensional (3d) Modelmentioning
confidence: 99%
“…In this case the strain rate is very low and the deformation is a quasi-static process, therefore the strain rate can be considered as a constant. In this study, the displacement rate is used to replace the strain rate [17][18][19][20][21]. The relationship between the strain rate and displacement rate is…”
Section: Cold Uniaxial Planar Compression (Cupc) Processmentioning
confidence: 99%
“…From the previous research [18][19][20][21], it is obvious that the lubrication can play an obvious role in hindering the surface asperity flattening. If the surface asperity flattening takes place at quasi-static (very low strain rate) process, the influence of lubrication is similar.…”
Section: Development Of Surface Asperitymentioning
confidence: 99%